Duodenal endoscopic submucosal dissection is feasible using the pocket-creation method - Miura, Yoshimasa; Shinozaki, Satoshi; Hayashi, Yoshikazu; Sakamoto, Hirotsugu; Lefor, Alan Kawarai; Yamamoto, Hironori (Endoscopy, 2017)
Background and study aims Duodenal endoscopic submucosal dissection (ESD) requires sophisticated endoscopic techniques because of a high rate of perforation. We introduced the pocket-creation method (PCM) of duodenal ESD to overcome difficulties. The aim of this study was to evaluate the safety and usefulness of ESD using the PCM for superficial tumors of the duodenum.Patients and methods We performed ESD of 17 non-ampullary duodenal lesions using the conventional method and of 28 lesions using the PCM from 2006 to 2015 and retrospectively reviewed the results, comparing the PCM and the conventional method. The median follow-up period was 35 months (range 2 – 97).Results There were more lesions at the duodenal angles in the PCM group compared with the conventional method group (54 % [15/28] vs. 22 % [4/17]; P = 0.048), and the resected specimen diameter was larger in the PCM than the conventional method group (median 37 mm [range 25 – 101] vs. 25 mm [15 – 55]; P = 0.007). Dissection speed was faster in the PCM than the conventional method group (9.4 mm2/min [3.0 – 15.7] vs. 6.5 mm2/min [1.5 – 19.7]; P = 0.09). En bloc resection was more frequent in the PCM (100 % [28/28]) than the conventional method group (88 % [15/17]) (P = 0.07). Perforation was significantly less frequent in the PCM (7 % [2/28]) than the conventional method group (29 % [5/17]; P = 0.046). The one delayed perforation in the conventional method group required surgical repair, while other intraprocedural perforations were treated by clipping. There were no recurrences.Conclusions ESD of duodenal lesions can be safely performed using the PCM, which stabilizes the tip of the endoscope even in difficult locations.